PROSEDUR DAN PENDEKATAN SISTEM TAFSIR BI AL MATSUR - Akbar, Ilham; Handayani, Ririn; Luthfiyyah, Siti Dhea (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
One aspect of Tafsir Al-Qur'an that can be used as a stepping stone for mapping interpretations is the source of interpretation that is used. The aim of this research is to describe the meaning, scope and differences of opinion among 'ulama regarding this interpretation, with the core problem raised by the author being the classification of Tafsir bi al Ma'tsur, whether it is classified based on sources, methods or styles of interpretation. This research uses a qualitative approach with data collection techniques using library research, then several problems raised are analyzed by the author so that clear results are obtained. We can know that Tafsir bi al-Ma'tsur is an interpretation that comes from clear history, it is also known as the earliest type of interpretation to appear in the treasures of Al-Qur'an interpretation. Until now, we can find the application of Tafsir bi al-Ma'tsur in the monumental works of scholars such as the books Tafsir Al-Thabari, Tafsir Ibn Katsir, Tafsir Ibn 'Athiyyah and others. The author's conclusion is that there are several 'ulama who mention Tafsir bi al-Ma'tsur as a style or even as a method of interpretation, but the majority of 'ulama classify Tafsir bi al-Ma'tsur into an interpretation classification based on sources.